Analysis of the Relationship between Midwives' Implementation of Vitamin K Administration and Compliance with Standard Procedures for Newborns at Bongo II Community Health Center - Ni Luh Diah Purnamasari; Widia Shofa Ilmiah (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2025)
Vitamin K administration is an essential component of standard neonatal care aimed at preventing bleeding disorders in newborns. Compliance with standard operating procedures (SOP) is a key indicator of the quality of neonatal services provided by midwives. This study aimed to analyze the relationship between vitamin K administration and compliance with neonatal SOP at Puskesmas Bongo II. A quantitative analytic study with a cross-sectional design was conducted from August to October 2025 involving 35 newborns selected using a total sampling technique. Data were collected through medical record review and observation sheets. Univariate analysis was used to describe newborn characteristics, while bivariate analysis was performed using Spearman’s rank correlation test. The results showed that most newborns received vitamin K (82.9%) and were managed in compliance with SOP (85.7%). Bivariate analysis revealed a strong and statistically significant relationship between vitamin K administration and SOP compliance (ρ = 0.898; p < 0.01). These findings indicate that proper vitamin K administration is closely associated with broader adherence to neonatal care standards. Although causal relationships cannot be inferred, the results highlight the importance of strengthening supervision, training, and monitoring of midwifery practices to improve the quality and consistency of neonatal care services.